Psychological Resilience in Latin America Nursing Students Using the Wagnild and Young Scale: A Scoping Review - Martinez, William Donegá; Filho, Marco Antonio Ribeiro; Casaleiro, Tiago; Rodrigues, Marcos Sanches; dos Santos, Emerson Roberto; Aleixo, Daniele Nunes Longhi; de Souza Menezes, João Daniel; da Silva, Matheus Querino; Ribeiro, Renato Mendonça; Nunes, Luiz Vianney Saldanha Cidrão; Franco, Rauer Ferreira; Spaziani, Amanda Oliva; et al. (MDPI, 2025)
Nursing students frequently experience considerable stress, impacting their mental well-being and preparedness for professional practice. Psychological resilience is paramount in navigating these demands. This scoping review synthesized studies on resilience levels in nursing students, particularly those in their entry year, utilizing the Wagnild and Young Resilience Scale within the Latin American academic context. Following JBI methodology and PRISMA guidelines, a systematic search identified six relevant studies. Findings indicate that newly enrolled nursing students often exhibit low to moderate resilience, which may decline during the first academic year. Importantly, resilience acts as a protective factor against psychoemotional stress, depressive symptoms, and poor sleep quality. Family support, engagement in leisure activities, and course satisfaction positively correlate with higher resilience. These findings underscore the imperative for educational institutions to actively integrate resilience-building strategies, such as curricular adjustments and psychoeducational programs, to bolster student well-being and cultivate competent future professionals. Further longitudinal research is essential to deepen understanding and evaluate intervention efficacy.